Vertical epistemic communities in multilevel governance. (27th July 2018) - Mavrot, Céline; Sager, Fritz
Abstract : Literature defines epistemic communities as knowledge-based networks whose purpose is to influence policy. While previous studies often focused on the horizontal functioning of epistemic communities, we expand the debate by integrating the vertical dimension as an additional governing structure. We argue that vertical epistemic communities take advantage of multiple-scale systems to generate coherent strategies which enable them to influence policymaking. Through the case of Swiss smoking prevention policy, we study how vertical epistemic communities in federalist systems can lead to policy harmonisation between member states. They do so by shifting the decision-making process away from the political towards expert arenas.